Sex-Specific Patterns of Diaphragm Phospholipid Content and Remodeling during Aging and in a Model of SELENON-Related Myopathy - Rezlène Bargui; Audrey Solgadi; Florent Dumont; Bastien Prost; Nathalie Vadrot; Anne Filipe; Andrew T. V. Ho; Ana Ferreiro; Maryline Moulin (Biomedicines, 2023)
Growing evidence shows that the lipid bilayer is a key site for membrane interactions and signal transduction. Surprisingly, phospholipids have not been widely studied in skeletal muscles, although mutations in genes involved in their biosynthesis have been associated with muscular diseases. Using mass spectrometry, we performed a phospholipidomic profiling in the diaphragm of male and female, young and aged, wild type and SelenoN knock-out mice, the murine model of an early-onset inherited myopathy with severe diaphragmatic dysfunction. We identified 191 phospholipid (PL) species and revealed an important sexual dimorphism in PLs in the diaphragm, with almost 60% of them being significantly different between male and female animals. In addition, 40% of phospholipids presented significant age-related differences. Interestingly, SELENON protein absence was responsible for remodeling of 10% PL content, completely different in males and in females. Expression of genes encoding enzymes involved in PL remodeling was higher in males compared to females. These results establish the diaphragm PL map and highlight an important PL remodeling pattern depending on sex, aging and partly on genotype. These differences in PL profile may contribute to the identification of biomarkers associated with muscular diseases and muscle aging.